Разработка пластикового формирующего элемента для медицинских электронных пучков - Бушмина Е. А. Елизавета Алексеевна; Булавская А. А. Ангелина Александровна; Григорьева А. А. Анна Анатольевна; Милойчикова И. А. Ирина Алексеевна (2022, 2022)
Заглавие с экрана